Characterization of Alien isoforms in vertebrates : Caracterización de isoformas de Alien en vertebrados - Tenbaum, Stephan; Justus Liebig University Giessen (My University, 2002)
Alien protein isoforms have been described to be involved in a number of biological processes. Alienalpha is a corepressor of the thyroidhormone receptor mediating transcriptional repression in a ligand-sensitive manner. Furthermore, Alienalpha is a corepressor for theorphan receptor DAX1 and the vitamin-D3 receptor. Alienbetta/CSN2 is part of the COP9-signalosome complex that acts in proteinphosphorylation, protein degradation and cell cycle regulation. The major goal of this work was to characterize the Alienalpha and Alienbetta isoforms. Little was known about their expression pattern andthe regulation of their expression had not been addressed. It was determined in this work that the expression pattern of Alien is rather ubiquitous in rat tissues. Interestingly, a putative novel Alienprotein isoform and an additional alien messenger specific for adrenal gland were identified. Furthermore, it was shown in vivo and in vitro,by in situ hybridization, Northern and Western blotting that Alien expression is regulated by thyroid hormone in the rat brain andbrain-derived cell lines. Subsequently, hints for a second T3-independent mechanism of regulation of Alien expression depending on cellconfluence or quiescence were discovered. The comparison of Alien isoforms in functional aspects identified Rb and E2F as novel Alien-interacting proteins with similar bindingcharacteristics in vitro and in yeast but functional differences in vivo. Alienbetta interfered with Rb-mediated superactivation of Sp1-driventranscription, whereas Aliena exerted strong repression on E2F transactivation. Common traits for both Alienalpha and Alienbetta are theirsilencing potential, interaction with TR and activation of AP1-driven transcription. Phosphorylation studies raised the possibility of regulation by non-hormonal signaling since Alienalpha and Alienbetta are phosphorylatedin vivo. In gel kinase assays suggested the existence of two different Alien-phosphorylating kinases. Further experiments identified MLK2and the cell cycle kinase p34cdc2 as such kinases, suggesting a possible function of Alien in cell cycle regulation. Taken together, the expression of Alien is regulated by thyroid hormone, and by cell density; the isoforms can be phosphorylated and canact either as transcriptional repressors or as activators. Additional data indicate a role of Alien isoforms in cell cycle regulation throughp34cdc2 phosphorylation and isoform-specific interference with Rb and E2F.
Charakterisierung von Alien Isoformen in Vertebraten
Keywords: ddc:570